Peningkatan Hasil Belajar IPS dengan Memahami dan Mengatasi Permasalahan Metode Pembelajaran - Muhammad Azril; Shiera Nada Nasuha; Bagus Setiawan (Institut Teknologi dan Bisnis (ITB) Semarang, 2024)
This research aims to explore and identify problems that arise in connection with learning methods in Social Sciences (IPS) subjects and to evaluate efforts to understand and overcome these problems in the educational context. Effective learning methods are considered one of the key factors in improving students' social studies learning outcomes. However, problems often arise that hinder the achievement of optimal learning outcomes. Efforts to overcome these problems include improving the selection of learning methods that are more appropriate to the educational context, increasing teacher training in designing and implementing effective learning, as well as continuous evaluation of methods. learning used. By better understanding the problems of learning methods in social studies education, it is hoped that solutions can be found that support improving student learning outcomes in this field.